2023
DOI: 10.5772/intechopen.109319
|View full text |Cite
|
Sign up to set email alerts
|

Congolese Traditional Foods as Sources of Antioxidant Nutrients for Disease Prevention

Abstract: Oxidative stress, characterized by excessive production of reactive species, is involved in several chronic diseases such as cardiovascular, chronic obstructive pulmonary, sickle cell, chronic kidney, neurodegenerative, and cancer. The negative impact of ROS and RNS, produced by endogenous and exogenous processes, is neutralized by antioxidant defenses. Given the importance of oxidative stress to human health, the use of antioxidants as therapy directs medical research toward the specificity of antioxidants ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Different parts of this plant used mainly as a condiment can, given its nutrient composition, contribute to the improvement of the physiological conditions of the organism. As far as minerals are concerned, they provide the organism with essential elements for protection and functioning and participate in specific metabolic reactions 41 . Calcium and phosphorus play an essential role in the formation of the skeleton.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Different parts of this plant used mainly as a condiment can, given its nutrient composition, contribute to the improvement of the physiological conditions of the organism. As far as minerals are concerned, they provide the organism with essential elements for protection and functioning and participate in specific metabolic reactions 41 . Calcium and phosphorus play an essential role in the formation of the skeleton.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…As to natural antioxidants, several studies reported their benefits in preventing oxidative stress and chronic non-communicable diseases like cancer, diabetes, cardiovascular disease, etc. 1,[7][8] . Recently, the use of natural antioxidants has been of great interest due to studies indicating the possible adverse effects associated with the consumption of synthetic antioxidants.…”
Section: Introductionmentioning
confidence: 99%